Artificial extracellular matrix delivers TGFb1 regulating myofibroblast differentiation. Issue 26 (23rd February 2016) - Cheng, Weilu; Xu, Ruodan; Li, Dalong; Bortolini, Christian; He, Jinmei; Dong, Mingdong; Besenbacher, Flemming; Huang, Yudong; Chen, Menglin
Abstract : Spatiotemporally controlled release of transforming growth factor β1 from electrospun biomimetic nanofibers realized optimal cell viability and myofibroblast differentiation capacity, which holds great potential in wound healing application. Abstract : During wound healing, the contractile activity of myofibroblasts differentiated from fibroblasts in active transforming growth factor β1 (TGFβ1) conditions has vital functions. In wound dressing biomaterials, it is crucial to mimic the extracellular matrix to deliver the right amount of TGFβ1 in a spatiotemporally controlled manner. We report here, for the first time, a zero-order, sustained TGFβ1 release from electrospun biomimetic nanofibers realizing optimal cell viability and myofibroblast differentiation capacity, confirmed by cell metabolic activity CCK assay, gene expression level through real-time PCR and protein expression level through immunochemical staining.